A qualitative study on barriers and strategies to hospital preparedness against chemical, biological, radiological, and nuclear incidents - Saeid Baikmohammadi; Bagher Amirheidari; Tania Dehesh; Mahmood Nekoei Moghadam; Vahid Yazdi-Feyzabadi; Ebrahim Hassani; Hossein Habibzadeh (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The effects of chemical, biological, radiological, and nuclear (CBRN) incidents on human society can be irreparable. Preparing the health system for these incidents is essential. This study aims to identify obstacles to hospital preparedness against CBRN incidents and provide solutions. MATERIALS AND METHODS: This qualitative study was conducted using semi-structured interview method in 2022. The research community included experts in the fields of CBRN, and 17 persons were included in the study through purposive sampling. The interviews were collected by interview guide and recorded face-to-face and online and were analyzed using thematic content analysis method in MS Word 2016. RESULTS: The interviews' analysis was classified into two main categories and 34 sub-categories. Some of the most important obstacles to the hospital preparedness against CBRN incidents were the lack of proper crisis management, the lack of specialist staff, the stress of employees, the lack of turnover and sufficient rest for employees, legal gaps, and so on. The main strategies were determining the type and extent of the risk factor, strong crisis management, the lack of parallelism, continuous monitoring, having a protocol and road map, appropriate training programs, having skilled personnel, rapid response of personnel, positive attitude of the staff, and the favorable condition of the building. CONCLUSION: The appointment of an expert in the field of CBRN and having a specialized unit, the existence of specialized and trained staff along with access to the required facilities, clear instructions, and intra-departmental and inter-departmental cooperation affect the readiness of hospitals against CBRN incidents.